Poisonous plants of paradise first aid and medical treatment of injuries from Hawaii's plants - Scott, Susan 1948-; Thomas, Craig 1952- (University of Hawaií Press, 2000)
A guide to potentially harmful plants in Hawaii, designed for both medical professionals and the general public. It describes each plant in words and photographs, identifies the plant's toxins, mechanism of injury, incidence, and signs and symptoms, and provides first aid recommendations.